2016
DOI: 10.1002/cncy.21768
|View full text |Cite
|
Sign up to set email alerts
|

Nodular fasciitis: A frequent diagnostic pitfall on fine‐needle aspiration

Abstract: BACKGROUND: Nodular fasciitis (NF) is a benign, self-limited, fibroblastic/myofibroblastic proliferation that is diagnostically challenging, often mimicking a malignant process due to its rapid growth clinically and its high cellularity, mitotic activity, and variable/nonspecific cytomorphologic findings. Herein, the authors report what to their knowledge is the largest and first multi-institutional study of the cytomorphologic characteristics of NF by fine-needle aspiration (FNA). METHODS:The pathology archiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“… These cases were previously published and described as cases 7, 9, 11, 12, and 13, respectively, in our prior study …”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“… These cases were previously published and described as cases 7, 9, 11, 12, and 13, respectively, in our prior study …”
Section: Resultsmentioning
confidence: 82%
“…A total of 15 cases involving the parotid gland were identified; they included 2 that were unavailable for cytomorphologic review and 5 that had been previously reported by the authors in a separate study but were re‐reviewed for inclusion in the current study . The demographics, clinical presentation, and FNA diagnoses for each case are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathologic diagnoses, cytomorphologic characteristics, immunocytochemical stains, and ISH studies were reviewed and recorded for all available cases. The overall specimen cellularity was assessed with a 4‐point scale like the one reported by Othman et al and used previously by Allison et al as follows: 1 = scant, 2 = hypocellular, 3 = moderately cellular, and 4 = hypercellular.…”
Section: Methodsmentioning
confidence: 99%